Current Issues in Tropical Plantation Forestry - a Malaysian Perspective - Abod, Sheikh Ali; Tahir Siddiqui, M. (Indian Forester, 1999)
World imports of wood and wood products have risen considerably and are likely to be robust, especially in pulpwood, chips and particle boards. The Asian Development Bank has analyzed raw material balance and estimated deficit to meet this demand. Plantations are considered to be more efficient than natural forests. In Malaysia exotics like Acacia mangium and Pinus caribaea have been mostly planted. Presently, stress by importing countries is being laid on environment friendly, well-managed tropical timbers and labelling of certificates is being insisted as well. In the light of these considerations new plantations to meet the deficit are being considered. Constraints like land, species selection, labour and finance have been discussed as well as privatisation and government policies and incentives and allowanccs by Government.